3rd TCMTs 2024 Book of Abstracts - Conference Scientific Committee (AlQalam Journal of Medical and Applied Sciences, 2024)
This is a collection of abstracts that was submitted for the participation in the 3r Tripoli Conference on Medical Technologies 2024 held by Faculty of Medical Technology, the University of Tripoli on October 12, 2024.